Prevalence of cervicovaginal human papillomavirus infection and genotypes in the pre-vaccine era in China: A nationwide population-based study. Issue 4 (April 2021) - Bao, He-Ling; Jin, Cheng; Wang, Shi; Song, Yi; Xu, Zhou-Yang; Yan, Xiao-Jin; Li, Li-Ming; Ning, Yi; Wang, Hai-Jun
Highlights: Prevalence of HPV infection was 15.0% in the pre-vaccine era in China. Vaccine-targeted HPV-52, -58, and -16 were most common in general population. HPV prevalence significantly differed across age groups and geographic locations. HPV prevalence is high and HPV vaccination strategy is needed in China. Summary: Objective: The HPV vaccine has been licensed in mainland China since 2017. This study aimed to assess the epidemiological characteristics of HPV genotypes in the pre-vaccine era in China. Methods: We conducted a multicentric population-based study nested in the largest health clinic chain in China. Between January 1, 2017 and December 31, 2017, 427, 401women aged 20 years or older with polymerase chain reaction-based HPV genotyping tests were included in the study. The cervicovaginal infection of 14 high-risk HPV genotypes and 9 low-risk genotypes was assessed using adjusted prevalence, multivariable logistic regression, cluster analysis, and heatmap. Results: HPV prevalence was 15.0% (95% confidence interval [CI]: 14.1–15.9%) in China, with high- and low-risk genotypes being 12.1% (95%CI: 11.4–12.7%) and 5.2% (95%CI: 4.8–5.7%), respectively. The prevalence of HPV genotypes corresponding to bivalent, quadrivalent, and nonavalent vaccines were 2.1%, 2.4%, and 8.3%, respectively, whereas the prevalence of non-vaccine high-risk genotypes was 5.7%. The most common high-risk genotypes were HPV-52 (3.5%), HPV-58 (2.1%), and HPV-16 (1.6%), and the prevalence of HPV-18 (0.6%), HPV-6 (0.1%), and HPV-11 (0.2%) were relatively low. Infection with HPV genotypes differed significantly across age groups and geographic locations. Conclusion: HPV prevalence was high in the pre-vaccine era in China, and a population-based HPV vaccination strategy is needed in the future.